Dynamic membrane changes and osmotic effects by sugar alcohols - Lichun Chen; Feng Yao; Songwen Xue; Kuang Yao; Yun Huang; Huimin Zhao; Qiong Shao (npj Science of Food)
Abstract Sugar alcohols are natural sweeteners with various physiological functions, commonly used in low-calorie foods and pharmaceuticals. Current research primarily focuses on their sweetening properties and metabolic effects, often overlooking their interactions with cell membranes. This study built a giant phospholipid vesicle model to examine vesicle deformation in erythritol (Ery) and xylitol (Xyl) environments. The permeation of these sugar alcohols through real cell membranes was also investigated. Fluorescence microscopy and zeta potential measurements showed that osmotic stress from concentration gradients disrupted vesicle membrane structure. Ery and Xyl reduced ROS levels in HEK-293 cells and influenced membrane permeability. Notably, Xyl increased vesicle adsorption on the cell membrane at the same concentration. The findings indicate that sugar alcohols interact with membrane lipids through hydrogen bonds or other non-covalent interactions, modifying cell membrane structure and properties, thus providing a theoretical foundation for understanding their role in physiological environments.